DETERMINATION VALUE OF SMUGGLING GOODS - Šaforostovs, Aleksejs (Administrative and Criminal Justice, 2015)
The aim of this Article is to evaluate determination of value of smuggled goods according to existing Latvian and EU legislation and regulations. The problem analyzed in this study- existing determination metodology of smuggled goods value, which does not comply with EU legislation and case law, and European Commission opinion as well. Article`s novity has been shown by research carried out through analysis of the smuggled goods value, paying special attention to Latvian legislation in comparison with EU law, the case-law. As particular novelty of research should be emphasized Author`s proposals for improvements in national legislation and terminology, defining specific activities. Summarizing up conclusions of the article it can be said that the value of smuggled goods should be fixed according to market price or assimilated price at the time of the offense, but it is not acceptable to include customs tax, VAT and excise tax into the value of goods. These taxes can be applied to determine the compensation for losses if it will be proved that goods had been intended for use in commercial purposes.